(untitled) (Transport systems and technologies, 2022)
The article puts forward a hypothesis according to which the violation of the nominal setting of wheel pairs in railway rolling stock carts is the main reason for the increase in guiding forces in the wheel flange contacts of the wheels of freight cars with the rails. Increased loads in wheel flange contacts are the cause of a number of other negative phenomena: increased intensity of wear (undercutting) of wheel flange, increased wear of the side surfaces of rail heads, decrease in the coefficient of stability of wagons from derailment, etc. To test this hypothesis, a study was conducted to obtain dependencies, first of all, these are the characteristics of the influence of geometric deviations of the position of the wheel pairs in the cart on the level of guiding forces in the contacts of the wheels with the rails and the wear of the wheel flanges. The relevance of this study is confirmed by data on the catastrophic wear of rails and solid-rolled wheels of wagons. An analysis of statistical data oblique setting of wheel pairs in carts in plan due to running-in of side frames was made, which shows that in 80% of wagons these angles can be up to 0,015 rad (0,85 degrees). The formula for the critical derailment ratio of the frame force to the vertical load on the wheel has been clarified, in contrast to Nadal’s formula, which additionally takes into account the deflection forces in the contact of the overlapping wheel.